ANALISIS POTENSI PANTAI GLAGAH SEBAGAI EKOWISATA UNGGULAN DI KABUPATEN KULONPROGO - Isdarmanto, Isdarmanto; Soebyanto, Oentoeng (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2018)
Glagah Beach is one of the most potential beaches and has the uniqueness as the charm and excellence of other southern seas. Glagah Beach located in Kulon Progo Regency is the only beach in Java that has a breakwater and has a lagoon on the edge of the sea separated by the sea so that large waves do not reach the lagoon. According to the typology of Glagah beach it self can be included in the classification of marine deposition coast. This is because the beach is formed due to the deposition deposition of river sedimentation material to the sea. This condition can be indicated by the emergence of a barrier coast emerging due to sedimentation from the river that empties into the location, then subject to marine effects that result in the formation of the lagoon. The process of sedimentation that occurs due to the flow and sedimentation of the river mouth that causes sedimentation in the coastal area. Qualitative research methods used with data collection techniques in the form of observation, interviews, documents, and various sources of data so it can be more clearly known geographical aspects of Glagah Beach, tourism profile, tourist visit conditions, tourism potential Glagah Beach, and to know the constraints which faced Glagah Beach tourism object and how the development strategy of Glagah Beach tourist attraction area in the future. Glagah Beach is a natural attraction that has the privilege and excellence compared to other beaches in Yogyakarta that need to keep the sustainability and need to be managed more effectively by the community and the local government as a policy holder so Glagah Beach became one of the leading ecotourism object which is interesting in Kulon Progo Regency Yogyakarta. Keywords: Glagah Beach; Sea Lagoon; Barrier Coast